Guided Autogenic Relaxation for Hypertensive Acute Pain: An Orem-Based Community Nursing Program - Dian Ratna Sari; Evy Aristawati; Apriana Rahmawati; Heny Ekawati (Tarqabin Nusantara Group, 2026)
Hypertension rarely presents in isolation; a substantial proportion of affected adults also live with acute pain, most often occipital headache and neck tension, that erodes daily functioning and pushes patients toward unsupervised analgesic use. Community-based, non-pharmacological interventions capable of addressing this dual burden inside patients' own homes remain underdocumented, particularly when explicitly grounded in a nursing theoretical framework. This community nursing program examined the effect of guided autogenic relaxation therapy, structured around Orem's Self-Care Deficit Theory, on acute pain intensity, blood pressure, and self-care behavior among hypertension patients in a primary care catchment area. A quasi-experimental, one-group pretest-posttest design, reported following TREND and TIDieR guidance, was applied to three male patients aged 49-56 years with moderate acute pain (Numeric Rating Scale 4-5). Each participant received a standardized 15-minute guided autogenic relaxation session daily for three consecutive days at home, with pain, blood pressure, vital signs, and pain-related behavior recorded before and after every session. Mean pain intensity fell from 4.67 to 1.33, a 71.5% reduction; systolic pressure declined by 21 mmHg and diastolic pressure by 13 mmHg; and observable pain behaviors resolved by the third day. Two of the three participants began practicing the technique independently before the scheduled session on day two, consistent with Orem's transition from a partially compensatory to a supportive-educative nursing system. These findings support incorporating guided autogenic relaxation into home-based community nursing as an accessible, theory-consistent strategy for strengthening self-care agency in hypertension management.